Phase Transformation of Adefovir Dipivoxil/Succinic Acid Cocrystals Regulated by Polymeric Additives - Jung, Sungyup; Ha, Jeong-Myeong; Kim, Il Won (MDPI AG, 2014)
The polymorphic phase transformation in the cocrystallization of adefovir dipivoxil (AD) and succinic acid (SUC) was investigated. Inspired by biological and biomimetic crystallization, polymeric additives were utilized to control the phase transformation. With addition of poly(acrylic acid), the metastable phase newly identified through the analysis of X-ray diffraction was clearly isolated from the previously reported stable form. Without additives, mixed phases were obtained even at the early stage of cocrystallization. Also, infrared spectroscopy analysis verified the alteration of the hydrogen bonding that was mainly responsible for the cocrystal formation between AD and SUC. The hydrogen bonding in the metastable phase was relatively stronger than that in the stable form, which indicated the locally strong AD/SUC coupling in the initial stage of cocrystallization followed by the overall stabilization during the phase transformation. The stronger hydrogen bonding could be responsible for the faster nucleation of the initially observed metastable phase. The present study demonstrated that the polymeric additives could function as effective regulators for the polymorph-selective cocrystallization.
Keywords: CRYSTALLIZATION; ENHANCEMENT; POLYMORPHS; CARBONATE; SELECTION; PRODUCTS; CRYSTAL; IMPROVE; DRUGS